2018
DOI: 10.1038/s41598-018-31908-2
|View full text |Cite|
|
Sign up to set email alerts
|

Hypoxia causes reductions in birth weight by altering maternal glucose and lipid metabolism

Abstract: Hypoxia of residence at high altitude (>2500 m) decreases birth weight. Lower birth weight associates with infant mortality and morbidity and increased susceptibility to later-in-life cardiovascular and metabolic diseases. We sought to determine the effects of hypoxia on maternal glucose and lipid metabolism and their contributions to fetal weight. C57BL6/NCrl mice, housed throughout gestation in normobaric hypoxia (15% oxygen) or normoxia, were studied at mid (E9.5) or late gestation (E17.5). Fetal weight at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 34 publications
(44 reference statements)
2
16
0
Order By: Relevance
“…(2016 ) reported that although embryos remained with weights similar to controls following exposure to more severe hypoxia, heart weight was lower. The maintained liver weight was in agreement with Määttä et al . (2018 ), who found no deviation in liver weight in mice subjected to hypoxia.…”
Section: Discussionsupporting
confidence: 90%
“…(2016 ) reported that although embryos remained with weights similar to controls following exposure to more severe hypoxia, heart weight was lower. The maintained liver weight was in agreement with Määttä et al . (2018 ), who found no deviation in liver weight in mice subjected to hypoxia.…”
Section: Discussionsupporting
confidence: 90%
“…The lower Hb levels associated with low-grade activation of the hypoxia-inducible factor (HIF) mediated transcriptional response, the HIF prolyl 4-hydroxylases (HIF-P4Hs) acting as the oxygen sensing component in this pathway. The HIF-mediated reprogramming of energy metabolism, leading to promotion of insulin-independent glucose intake and upregulation of the non-oxygen demanding glycolytic metabolism and downregulation of oxidative phosphorylation, has been shown to mediate protection against obesity and metabolic syndrome resulting in reduced body weight and adiposity, lower serum cholesterol levels, less white adipose tissue inflammation and improved glucose tolerance and insulin sensitivity in human and mice, also during gestation 13 , 33 , 34 . Combining the results of this study, we offer HIF activation as a potential mechanism behind the protective effect of the lower-end normal Hb levels and decreased risk for GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in rodents have evaluated the effect of different levels of inhalation hypoxia on maternal metabolic support of fetal growth. Pregnant mice maintained under 15% hypoxia from the start of pregnancy show reduced maternal weight gain and adipocyte area during gestation (Määttä et al 2018). They also show greater glucose tolerance, fail to acquire insulin resistance and have elevated serum glucagon levels in late pregnancy (Määttä et al 2018).…”
Section: Low Protein Dietmentioning
confidence: 99%